Pengaruh Kesehatan Keselamatan Kerja (K3) dan Disiplin Kerja Terhadap Kinerja Karyawan: Survei pada PT. Bank Sinarmas Kota Sukabumi - Luki Abdul Hakim S; R. Deni Muhammad Danial; Faizal Mulia Z (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to find out how much influence occupational health and safety (K3), work discipline has on the performance of PT employees. Bank Sinarmas Sukabumi City. The 40 respondents in this research were employees of PT. Bank Sinarmas Sukabumi City. This research method uses quantitative methods with descriptive and associative approaches. In the research, a normality test, a simultaneous statistical test (F test) and a partial statistical test (T test) were carried out. The results of the research show that there is a simultaneous positive influence between occupational health and safety (K3), work discipline and employee performance, with a result of 16,539 > 3.25, which means the calculated F value is greater than F Table. Meanwhile, partially, occupational health and safety (K3) has a positive and significant effect on employee performance, this is proven by the value obtained from the T Calculation results, which is 2,021, which is greater than the T Table, which is 1,684, with a significance value of 0.000 < 0.05. And work discipline has a positive and significant effect on employee performance, this is proven by the value obtained from the T Calculation results, which is 5,747, which is greater than the T Table, which is 1,684, with a significance value of 0.000 < 0.05